Everolimus for Compassionate Use in Multiple Basal Cell Carcinomas. (23rd September 2013) - Eibenschutz, Laura; Colombo, Delia; Catricalà, Caterina
Abstract : Everolimus is an inhibitor of the mammalian target of rapamycin (mTOR) and has been shown to have antineoplastic activity in addition to its use as an immunosuppressive agent for the prevention of organ transplant rejection. We report the use of everolimus for the compassionate treatment of four elderly, nontransplant patients presenting with multiple basal cell carcinomas (BCC). All patients had a long history of BCC, had refused surgery as a current treatment option, and did not respond to alternative treatments (including topical 5-fluorouracil and imiquimod). Patients were treated with oral everolimus (1.5–3.0 mg daily) for 12 months or longer: a complete and sustained response was seen in one case, and partial responses were seen in two other cases. Everolimus was well tolerated in these elderly patients. These promising preliminary data suggest that further dose-finding, controlled clinical studies are warranted to evaluate the antineoplastic effects of everolimus in patients affected by BCC who cannot or will not undergo surgery.